PENERAPAN SENSOR ULTRASONIK PADA SISTEM PENGISIAN ZAT CAIR DALAM TABUNG SILINDER BERBASIS MIKROKONTROLER ATmega 16 - Wiharto, Holy Lydia; Yuliananda, Subekti (JHP17 (Jurnal Hasil Penelitian), 2016)
Ultrasonic sensor has the ability to measure the distance to an object up to 300 cm by emitting ultrasonic waves. Ultrasonic waves emitted propagating in air at the speed of sound waves 344m / sec. Reflected wave is used to detect the object distance. By using a microcontroller as a data processing, a liquid comprising system can be created. Microcontroller can control the motor dreiver relay to activate the pump to fille the tube and stop it if the liquid level in cylindrical tube has been reached. This system uses ultrasonic sensors GH-311, the microcontroller ATmega16, and a dc motor. The test results show, in general, GH-311 ultrasonic sensor can be applied to read the distance to the surface of the liquid, in detection range of 2cm-300cm. The system works and keep filling the tube during the waterlevel in the tube has not reached 17 cm (as setting point). The water pump stops once the water level has exceeded 17 cm.Keywords: Ultrasonic Sensor, Microcontroller, control, automatic